The impact of electronic product use on children with tic disorders and ADHD, and management strategies: a review - Zhang, Yi; Zhang, Jiaqi; Yu, Xiaolu; Zhang, Jie; Xu, Yan; Cui, Hongtao (Frontiers in Psychiatry, 2025)
The pervasive use of electronic products raises significant neurodevelopmental concerns for children with Attention Deficit Hyperactivity Disorder (ADHD) and Tic Disorders (TDs), a vulnerable population particularly susceptible to the negative impacts of electronic products and at higher risk for problematic usage patterns. The clinical management of this issue is challenged by an incomplete understanding of the impact mechanisms. A review of the literature reveals these effects are complex and primarily functional, affecting systems like dopamine and executive functions, rather than causing widespread organic brain damage. Since the severity of the impact varies and absolute prohibition is often not the best approach, scientific management that focuses on content, duration, and usage patterns is essential. Specific, well-managed digital content may even have neutral or beneficial effects. Therefore, the paradigm for managing electronic product use must shift from simplistic restriction to scientific guidance and individualized strategies. This review offers an evidence-based framework to help clinicians tailor advice for each child’s developmental profile, moving beyond generic restrictions to foster healthy development in the digital age.